Assessment of Adaptive Reuse of Heritage Shop Houses for Sleep Lodging in Malaysia: Fulfilment of Conservation Guidelines - Othuman Mydin, M.A.; Keling, N.A.; Md. Sani, N.; Abas, N.F (EDP Sciences, 2014)
This study focuses on the compliance of adaptive reuse of historic shop houses for sleep lodging with reference to the Guidelines for Conservation Areas and Heritage Buildings by Majlis Perbandaran Pulau Pinang (MPPP). Through this research, awareness towards the compliance of building conservation guidelines for heritage shop houses will be clarified accordingly. The goal of this study is to determine and extract vital clauses and components of Guidelines for Conservation Areas and Heritage Buildings (GCAHB) towards adaptive reuse of heritage shop houses so that revitalization of these buildings can be ensured when changing the original function of the property. The aim is also to evaluate the compliance of the adaptive reuse of heritage shop houses with the GCAHB, and, lastly, to provide recommendations for adaptive reuse of heritage shop houses, also in compliance with the GCAHB. Additionally, heritage building owners can use this dissertation as a reference whenever they intend to adaptively reuse their buildings. Furthermore, recommendations in this research could be used for future reference.